Internet connectivity disruption in Yemen (Yemen) - Voidly (2026)
CRITICAL severity disruption detected in Yemen. Confidence: 65%. Data sourced from IODA.
Network Disruption Incident ID: YE-2026-0028
Keywords: internet disruption; YE; disruption; critical